Mutation profiling in South African patients with cornelia de lange syndrome phenotype using targeted next generation sequencing - Seymour, Heather (My University, 2019)
Cornelia de Lange Syndrome (CdLS) is a monogenic, heterogeneous, congenital disorder. Its main features are intellectual and developmental delay, failure to thrive and skeletal abnormalities. It displays a wide phenotypic range and has a significant phenotypic overlap with other conditions resulting in multiple differential diagnoses. To date, mutations in five genes have been reported to cause CdLS, accounting for 70% of clinically diagnosed patients. These genes are involved in the cohesin pathway. The remaining 30% of cases could either harbour a mutation in another gene, potentially also in the cohesin pathway, in a regulatory region or patients with a less classical phenotype could have been misdiagnosed owing to the broad phenotypic spectrum. Currently no molecular studies have been carried out on patients with CdLS in South Africa and thus the molecular cause of this disease is unknown in this population. This study aimed to use a targeted next generation sequencing technique to study the molecular aetiology of CdLS in South African patients and families. By adopting this technique, we were able to study multiple genes simultaneously to elucidate the mutation profile of this condition in a South African setting. Our gene panel included the five known causal genes as well as genes implicated in the differential diagnoses and other genes involved in the cohesin pathway. Out of the 14 patients that underwent targeted sequencing, putative disease-causing mutations were identified in eight. These were classified as pathogenic using the ACMG guidelines in addition to other bioinformatic tools and databases. Four of these mutations were small deletions, one was a single base pair duplication, one was a splice site mutation and two were missense mutations. The phenotypes of these eight patients correlated in severity in accordance with other genotype-phenotype studies that have been conducted in the past. Seven of the mutations were identified in the NIPBL gene, the most commonly mutated gene in CdLS. The remaining mutation was identified in STAG1. At the time of designing the targeted gene panel, no mutations had been identified in STAG1 in humans. This gene is involved in the cohesin pathway and was only suspected to be involved in CdLS. This study provides novel insights into the mutation profile of CdLS in South African patients. Studies such as this can inform the development of diagnostic techniques involving next generation sequencing panels as well as offering testing options for patients with CdLS in South Africa.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019